PEASANT WOMEN:: PROTAGONISM IN THE CONSTRUCTION OF THEIR TERRITORIES (Interdisciplinary Studies Journal, 2025)
The general aim of this study is to understand the influence of peasant women in the process of shaping the territory of a rural community in Pará. To this end, the methodological procedure made use of oral history. The participants were a teacher and six peasant women, the oldest residents of the community. The results show that the peasant women's way of life and work have an intrinsic relationship with nature and agriculture, with cassava being the predominant crop in the territory. Traditional knowledge, built up throughout their history through observation and experimentation, is passed down from generation to generation, with women playing a key role in this process. The study gave voice to some of these women and reaffirms the importance of them being heard. In addition, it also highlights that rural education is an essential area of struggle to ensure the recognition of female protagonism, which contributes significantly to the culture and identity of the territory.
Keywords: Rural Education; Gender Struggles; Memory; Orality; Identity